INFORMATION ON RELATIONS WITH BORDERING COUNTRIES IN THE DOCUMENTS OF THE TURKESTAN GOVERNOR-GENERAL'S COURT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article examines the issues of relations between the regions of the Turkestan General-Governorate and neighboring states. Using the reports of the military governors of the Transcaspian and Semirechye regions as an example, information is given on relations with Afghanistan, Iran and China. The features of relations with neighboring states in the period of the second half of the 19th – early 20th centuries are studied. The main sources were the office materials of the Governor-General's Office. These materials are stored in the funds of the Central State Archives of the Republic of Uzbekistan.